Grin and Barre It: Building Healthy Students in Physical Education. (25th November 2020) - Bruno, Laura E.; Farrell, Anne
Abstract : Barre fitness classes are ballet-inspired challenges that incorporate ballet barre and ballet positions. This non-traditional lifetime fitness activity is appropriate for a vast array of student learners. Non-traditional units can be defined as new or different from established norms and methods. Physical educators should consistently integrate a variety of units to offer student choice regarding their physical activity options. This article will support professionals with the implementation of a lifetime wellness, non-traditional Barre unit in Physical Education.